(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1995)
The present paper describes the species Pseudobuangia chitralica, Yatsengia hangchowensis, ? Protomichelinia multitabulata multitabulata, Protomichelinia guizhouensis flexuosa, Protomichelinia siyangensis and Sinopora ? cf. syrinx from the Baroghil region of NW Pakistan. The fauna originates from different levels, from the Sakmarian to the Artinskian, or even a more younger.